Marine Geodesy in the Department of Defense (USA) - Beaton, Robert J. (The International Hydrographic Review, 2015)
Marine geodesy during and since World War II has occupied a significant place in the military whenever precise positioning or distance measurements were required. Applications of geodetic principles in coastal and deep ocean marine environments have been of perhaps greater importance to the Naval Oceanographic Office (NAVOCEANO) and the Defense Mapping Agency (DMA) in DoD. The Army Corps o f Engineers depends also on accurate geodetic control in the conduct of hydrographic survey and dredging operations in United States harbors and inland waterways. Accurate absolute positions are critical for Air Force global operations using electronic navigation systems referenced to the World Geodetic System (WGS). Even the Department of State depends on DMA and the National Ocean Service (NOS) for Doppler-derived island positions and computed geodesics to determine Exclusive Economic Zone (EEZ) 200-mile limits from continental baselines and median lines between U.S. and foreign territories. Other navigational problems demanding precise geodetic control are associated with radioactive waste disposal and missile-firing evaluations. The aim of this paper, therefore, is to review major marine geodetic requirements, relevant applications, and major developing systems, some o f which are being developed for DMA through the Naval Ocean Research and Development Activity (NORDA).